ANALISIS PERAMALAN PENJUALAN PRODUK FURNITURE DI PT. KATWARA - Akhmad Adi Susatyo; M Jufriyanto; Akhmad Wasiur Rizqi (LPPM Politeknik LP3I Medan, 2022)
In the era of globalization, the development of the industrial sector is advancing rapidly. With the development of the economy in Indonesia, the need for furniture or household furniture is increasing. Pt Katwara is a company that sells furniture needs in Gresik Regency, East Java. In the erratic sales of a product every month, it is difficult for the company to determine product sales targets every month. With these sales problems, companies really need a sales solution that can forecast product sales every month Forecasting is a method used to estimate a future value using past data. In this study, the author discusses the analysis of forecasting sales of furniture products at PT. Katwara for this type of chair product. Forecasting is done using three methods, namely the Moving Average method for periods I, II, and III, the Exponential Smoothing with Trend method, and the Trend Analysis method by comparing the smallest error rate, the selected forecasting method is the Moving Average method with Period I. The Moving Average method with Period I has a MAD (Mean Absolute Deviation) value of 171.532, MSE (Mean Absolute Deviation) of 56789.49, MAPE (Mean Absolute Percent Error) 68.248%, and Bias of 1.957 while the standard error is 243.544. From the analysis of data processing that has been carried out based on the selected forecasting method, the sales forecast for the chair-type furniture product is 120 pieces, meaning that PT. Katwara must provide 120 chair-type furniture raw materials for the next period.